Financial Crime in the Operational Work of the State Security Service Until 1956 – Lower Silesian Perspective - Klementowski, Robert (Studia Historiae Oeconomicae, 2016)
Nationalization and the introduction of state-controlled economy led to the emergence of abnormal social phenomena, including system-specific crimes. Economic transformations were the foundation of the systemic revolution carried out in the first decade after the Second World War, therefore they were the subject of interest for the Ministry of Public Security. That is why financial crimes were treated just like political crimes, which was also justified by legal provisions, as no specific definition of this type of crime existed. This allowed the authorities (secret police, prosecutor’s office, courts, media) to interpret the events according to their will and current political needs, and, as a result, to administer various overt or covert repressions (death penalty, imprisonment, forced cooperation with the secret police).